Efecto de los extractos de membrana de merozoitos de plasmodium falciparum sobre la yema de huevo de gallus gallus - Cruz Bueza, Fredy Luis (2009)
The aim of this study is to induce specific antibody IgY in Gallus gallus immunized with membrane extracts of merozoites of Plasmodium falciparum. Three groups were formed from 2 hens each, the first group was inoculated intravenously 0.5 mL. membrane extracts of Plasmodium falciparum merozoites. , Another group with 1.0 mL. membrane extracts of Plasmodium falciparum merozoites., having also a control group who is 1.0mL inoculum. physiological saline. Eggs were collected daily and stored in refrigeration at 4 oC, we proceeded to work with eggs from 15 days post inoculation. Ig Y was purified with PBS deslipidación And - Chloroform and fractional protein precipitation with ammonium sulfate. We evaluated the immunoglobulin concentration (mg / ml) of egg yolk with the method of Brandford. Were analyzed by western blot, which revealed 2 bands with relative masses antigen between 42 and 19 kDa recognized by the immunoglobulins synthesized by hens immunized with the membrane extract of Plasmodium falciparum Merozoite. For facility and economy of the anti IgY antibody production membrane of Plasmodium falciparum Merozoite in egg yolk of Gallus gallus recommend this technique for detecting the parasite in the blood of infected patients. Data from this study demonstrate the presence of significant antigenic bands of membrane extracts of merozoites of Plasmodium falciparum.